Longitudinal Changes in Sarcopenia Criteria in Older Men with Low Skeletal Muscle Mass Index: A 2-Year Observational Study - Kemmler, Wolfgang; von Stengel, Simon; Kast, Stephanie; Sieber, Cornel; Freiberger, Ellen (Journal of Science in Sport and Exercise, 2019)
Purpose: Declines in muscle mass and function are inevitable during the aging process. However, what is the “normal age appropriate” decline of muscle mass and function? Further, is this decline uniform for muscle mass versus functions or between different functional abilities? Using recognized Sarcopenia criteria [i.e. skeletal muscle mass index (SMI) defined as appendicular skeletal muscle mass/height (kg/m2), handgrip strength, gait velocity], the aim of the present project was to determine corresponding changes in community-dwelling men 70 years+ with low SMI over a 2-year period. Methods: One hundred and seventy-seven (177) men within the lowest SMI quartile of a recent epidemiologic study (n = 965) were included in the 2-year follow-up analysis. Muscle mass was determined via direct-segmental, multi-frequency Bio-Impedance-Analysis, handgrip strength was tested with a Jamar hand-dynamometer and habitual gait speed was assessed with photo sensors applying the 10 m protocol. Results: SMI, handgrip strength and gait velocity all declined significantly (P< 0.001; effect size, d′ 0.39–1.17), however, with significantly higher reductions (P< 0.001) in functional compared with morphologic Sarcopenia criteria (P ≤ 0.006). Less expected, handgrip strength featured a fourfold higher decline compared with gait velocity (− 12.8 ± 10.9% versus − 3.5 ± 9.0%). Conclusion: We provided evidence for significant non-uniform changes of Sarcopenia criteria in a cohort of community dwelling men 70 years+ with low SMI. We doubt that this result might be a particularity of the selected cohort; however, studies with other (older) cohorts should address this issue in more depth. Of practical relevance, our data further give implications for the prioritization of interventions that address Sarcopenia criteria in older community-dwelling men.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Aging; Gait velocity; Handgrip strength; Muscle mass; Older men; Sarcopenia